INDUKSI MUTASI DENGAN IRADIASI SINAR GAMMA DAN SELEKSI IN VITRO UNTUK MENDAPATKAN EMBRIO SOMATIK KACANG TANAH YANG TOLERAN POLIETILENA GLIKOL - Hemon, A. Farid (JURNAL AGROTROPIKA, 2020)
The objectives of this experiment were to evaluate effectiveness of Gamma ray to somatic embryos culture to increase frequency of obtaining polyethylene glycol (PEG) insensitive somatic embryos (SE) of cv. Local Bima peanut. The experiment was inisiated with induction of peanut SE. Mutation induction was done on SE culture. Somatic embryos that have been irradiated with Gamma ray were selected in medium containing polyethylene glykol 15% (PEG 6000). Results of the experiment achieved, namely: 1) Gamma ray dosage affected peanut SE growth. Higher Gamma ray dosage used, it was more inhibited peanut SEs growth. Use of IS Gy dosage gave SEs growth better than up dosage, 2) embriogenic calli irradiated with Gamma ray dosage 15 and 20 Gy showed high SE proliferation, high number of SE per explant, high SE total when selected in medium containing PEG 15%, and lower SE growth occured on SE calli without irrardion and dosage 25 Gy. Key words: Mutation, Gamma ray